2013
DOI: 10.3390/cancers5041413
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of siRNA Nanoparticle Formation Using Mono-Cationic Detergents and Its Use in Gene Silencing in Human HeLa Cells

Abstract: The focus of recent research has been on the development of siRNA vectors to achieve an innovative gene therapy. Most of the conventional vectors are siRNA nanoparticles complexed with cationic polymers and liposomes, making it difficult to release siRNA. In this study, we report on the use of MCD, a quaternary ammonium salt detergent containing a long aliphatic chain (L-chain) as an siRNA complexation agent using human HeLa cells (a model cancer cell). We prepared siRNA nanoparticles using various MCDs, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…To date, we have been successful in efficiently packaging nucleic acids, including oligo DNA [13,14] and siRNA [15,16], and showed that the MEND system achieved efficient gene silencing and RNA knockdown [14][15][16][17][18][19]. These results prompted us to consider the possibility that a MEND system could be used to achieve the efficient cytosolic delivery of nucleic acids targeted to impregnable MIN6 cells.…”
Section: Introductionmentioning
confidence: 99%
“…To date, we have been successful in efficiently packaging nucleic acids, including oligo DNA [13,14] and siRNA [15,16], and showed that the MEND system achieved efficient gene silencing and RNA knockdown [14][15][16][17][18][19]. These results prompted us to consider the possibility that a MEND system could be used to achieve the efficient cytosolic delivery of nucleic acids targeted to impregnable MIN6 cells.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of gene silencing efficiency (%) of ticks injected with longicin dsRNA compared to Luc dsRNA-injected ticks was calculated as follows: Gene silencing efficiency (%) = (1–L Long /L Luc ) × 100. Where, L Long and L Luc represent the normalized longicin expressions of longicin dsRNA-injected and Luc dsRNA-injected ticks, respectively [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Inorganic functional nanomaterials have emerged as reliable and adaptable nano scaffolds for gene delivery [ 1 , 2 ]. The synthesis of numerous primary proteins in microbes and living cells is the focus of cutting-edge recombinant techniques that have replaced outdated methods and the current trends in bio-nanotechnology.…”
Section: Introductionmentioning
confidence: 99%